2017
DOI: 10.15406/hij.2017.01.00003
|View full text |Cite
|
Sign up to set email alerts
|

Delphinium malabaricum (Huth) Munz. : A Potential Ornamental Crop from Western Ghats

Abstract: Delphinium malabaricum (Huth) Munz. (Ranunculaceae), the only species of the genus Delphinium growing naturally in Western India, is endemic to Northern Western Ghats of Maharashtra. It produces beautiful and attractive spurred flowers of violet blue color with splendid green rosette foliage. Herein, we report our preliminary observations relating to seed germination, growth performance and post harvest performance of cut flowering stems of this plant. The annotations revealed that the seeds germinated through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…On the other hand, in our study, for D. elatum the DW of the leaves was determinant in the TPDW along all the life cycle, with an average of Phenology of Solidago canadenSiS l. and delphinium elatum cultivated under greenhouse conditions and association with micro-climate variables 362 20 leaves/plant. This result is corroborated by Kolar et al (2017), referring to Delphinium malabaricum, where they reported numerous (18-34) palmatisect leaves with long petiole.…”
Section: Development and Growth Of Flower Crops Under Greenhouse Cond...supporting
confidence: 67%
See 1 more Smart Citation
“…On the other hand, in our study, for D. elatum the DW of the leaves was determinant in the TPDW along all the life cycle, with an average of Phenology of Solidago canadenSiS l. and delphinium elatum cultivated under greenhouse conditions and association with micro-climate variables 362 20 leaves/plant. This result is corroborated by Kolar et al (2017), referring to Delphinium malabaricum, where they reported numerous (18-34) palmatisect leaves with long petiole.…”
Section: Development and Growth Of Flower Crops Under Greenhouse Cond...supporting
confidence: 67%
“…For D. elatum, natural light was sufficient for plant development which responds best to mean temperatures between 18 to 21 °C (Hanks, 2016). Similarly, Kolar et al (2017) mention that delphinium germinates very well at temperatures ranging between 23 ºC to 25 ºC during June, July and August when the relative humidity is very high in southern India.…”
Section: Development and Growth Of Flower Crops Under Greenhouse Cond...mentioning
confidence: 92%
“…Las soluciones evaluadas mantienen un medio ácido que tiene como efecto principal bajar la tasa de multiplicación de microorganismos, y por ende, retarda el efecto taponamiento de haces conductores que impide el ascenso de agua como fue demostrado por Van Doorn et al (1990). Por otra parte, en la medida en que se diluyó la cantidad de Sprite en las soluciones, disminuye el contenido de azúcar de las mismas, elemento que ha probado ser un sustrato de mantención de la actividad metabólica de los tallos cortadas aun cuando incremente la posibilidad de desarrollo de microorganismos (Kolar et al, 2017). Hay abundante literatura que respalda el uso de pH ácidos y azúcar en la pos cosecha de flores (Nowak y Rudnicki, 1990).…”
Section: Figura2unclassified